Prediksi Emisi Karbon Dioksida Dari Kegiatan Transportasi Di Kecamatan Bukit Raya Kota Pekanbaru - Muhammad Iqbal; Aryo Sasmita; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The population of Pekanbaru City grows increasingly every year, especially in Bukit Raya Sub-district. The higher number of motorcycle used by the people as a transportation directly affect the amount of CO2 emissions generated from each vehicles. This study aims to calculate the volume of vehicles and predict CO2 emissions from the number of vehicles in Bukit Raya District. The methodology used in this study is the calculation of the number of vehicles on Sudirman Street, Teuku Bey and Karya I, the calculation of the conversion of the number of vehicles with units of passenger cars (SMP), and calculation of CO2 emissions on effective and non effective day in Bukit Raya District. Total emissions generated from transport activities in Bukit Raya District are 422 ton CO2 / day on effective day and 241,46 ton CO2 / day on non effective day.Keywords: Carbon Dioxide Emissions, Passenger Car Unit (SMP), Emission Factor, Transportation.